Public Relations in the Arts, Liesure and Entertainment Fields (Uk Experience) - Nilufar, Maratova (PT. Antis International Publisher, 2024)
This article aims to introduce students to public relations in the fields of arts, recreation and entertainment. The role of public relations and the strategies and tactics required by arts and recreation organizations were then explored using a variety of contemporary case studies. Then trends and issues affecting public relations in the sector, such as the rise of celebrity, were analyzed.